2022
DOI: 10.1128/iai.00369-22
|View full text |Cite
|
Sign up to set email alerts
|

Legionella pneumophila Cas2 Promotes the Expression of Small Heat Shock Protein C2 That Is Required for Thermal Tolerance and Optimal Intracellular Infection

Abstract: Previously, we demonstrated that Cas2 encoded within the CRISPR-Cas locus of Legionella pneumophila strain 130b promotes the ability of the Legionella pathogen to infect amoebal hosts. Given that L. pneumophila Cas2 has RNase activity, we posited that the cytoplasmic protein is regulating the expression of another Legionella gene(s) that fosters intracellular infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 133 publications
0
3
0
Order By: Relevance
“…Normally, rhizobium genome encodes 4 degP proteins, which have been implicated in stress responses (Glazebrook et al ., 1996). hspC2, on the contrary, is a small heat shock protein known to be important for bacterial resistance to high temperature in bacteria (Campbell & Cianciotto, 2022). Interestingly, the expression of degP3 and hspC2 are probably controlled by the same operon in rhizobia (Narberhaus et al ., 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Normally, rhizobium genome encodes 4 degP proteins, which have been implicated in stress responses (Glazebrook et al ., 1996). hspC2, on the contrary, is a small heat shock protein known to be important for bacterial resistance to high temperature in bacteria (Campbell & Cianciotto, 2022). Interestingly, the expression of degP3 and hspC2 are probably controlled by the same operon in rhizobia (Narberhaus et al ., 1998).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, they con rm que VapD has a cleavage site of the mRNA before adenine (A) and guanine (G), indicating that it has purine-speci c endoribonuclease activity [9]. On the other hand, studies done in Legionella pneumophila have showed that Cas2 play an important role in promotes the expression of several proteins, among them a small heat shock protein C2 (HspC2) required for thermal tolerance and the intracellular infection in Acanthamoeba castellanii, in uencing in the virulence and physiology of the bacterium [19]. Gunderson et al, determined that Cas2 protein is indispensable for Legionella pneumophila to successfully infect the amoebae and it has RNasa and DNasa activities, reinforcing the published for other authors, who demonstrated that the Cas proteins have other different role to phage/plasmid immunity [20], as it is known, the Cas2 protein participates in the stress response in Mycobacterium tuberculosis [21].…”
Section: Discussionmentioning
confidence: 99%
“…All primers and plasmids used in this study are listed in Supplementary Data 3 and 4 , respectively. To make the L. pneumophila NU468 and NU469 mutant strains that have a nonpolar, unmarked deletion within the lcl gene, we employed overlap extension PCR (OE-PCR) followed by allelic exchange, as before 13 , 62 . DNA fragments of the 5′ and 3′ regions flanking the lcl ORF were PCR-amplified from 130b DNA using the primer pairs lcl -UpF and lcl -UpR for 5′ lcl , and lcl -DownF and lcl -DownR for 3′ lcl .…”
Section: Methodsmentioning
confidence: 99%